Оптимізація споживання електроенергії на електричному транспорті з використанням інформації автоматизованої системи комерційного обліку електроенергії - Bityukov S.D.; Kuznetsov V.G.; Sychenko V.G. (General Energy Institute of the National Academy of Sciences of Ukraine, 2011)
In power supply systems of railways, there are very considerable reserves for reducing the power losses due to the introduction of rational modes of a system of traction power supply. The automated systems of commercial electric power accounting can serve not only for their classic purposes, but they can also create conditions for the control over modes in power supply systems. We propose a target function for the task to control the modes of a power supply system for electrified transport. This function allows one to consider the time variability of a tariff of consumed electric energy, as well as the reliability of switching devices, transformers, and poles of contact lines. At the Donetsk railway, we carried out the experimental verification of the proposed theoretical concepts concerning the regulation of a voltage on the busbars of traction substations.